2017
DOI: 10.3390/w9100778
|View full text |Cite
|
Sign up to set email alerts
|

A Keystone Methylobacterium Strain in Biofilm Formation in Drinking Water

Abstract: Abstract:The structure of biofilms in drinking water systems is influenced by the interplay between biological and physical processes. Bacterial aggregates in bulk fluid are important in seeding biofilm formation on surfaces. In simple pure and co-cultures, certain bacteria, including Methylobacterium, are implicated in the formation of aggregates. However, it is unclear whether they help to form aggregates in complex mixed bacterial communities. Furthermore, different flow regimes could affect the formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…This supports previous observations from UK DWDS, where a core bacterial community in biofilms was observed independently of the characteristics of the incoming water or localised conditions between sites (Douterelo et al, 2017(Douterelo et al, , 2018(Douterelo et al, , 2020. Similar observations were proposed by other researchers from different countries like Germany, USA Portugal or China studying mixed species biofilms (Henne et al, 2012;Kelly et al, 2014;Ling et al, 2016;Rickard et al, 2004;Simões et al, 2007Simões et al, , 2008Tsagkari et al, 2017). In these studies, bacteria belonging to genera like Acinetobacter, Burkholderia, Methylobacterium, Mycobacterium, Pseudomonas, Sphingomonas and Staphylococcus played an important role in the formation of biofilms and aggregates.…”
Section: Microbiological Characteristics Of the Water Samples Containing Materials Removed From Distribution Systemsupporting
confidence: 91%
“…This supports previous observations from UK DWDS, where a core bacterial community in biofilms was observed independently of the characteristics of the incoming water or localised conditions between sites (Douterelo et al, 2017(Douterelo et al, , 2018(Douterelo et al, , 2020. Similar observations were proposed by other researchers from different countries like Germany, USA Portugal or China studying mixed species biofilms (Henne et al, 2012;Kelly et al, 2014;Ling et al, 2016;Rickard et al, 2004;Simões et al, 2007Simões et al, , 2008Tsagkari et al, 2017). In these studies, bacteria belonging to genera like Acinetobacter, Burkholderia, Methylobacterium, Mycobacterium, Pseudomonas, Sphingomonas and Staphylococcus played an important role in the formation of biofilms and aggregates.…”
Section: Microbiological Characteristics Of the Water Samples Containing Materials Removed From Distribution Systemsupporting
confidence: 91%
“…It can be suggested that these microorganisms form a core community and play a key role in biofilm formation, as proposed by other researchers studying mixed-species biofilms [72][73][74][75][76][77] . In these studies, bacteria belonging to the genera Acinetobacter, Burkholderia, Methylobacterium, Mycobacterium, Sphingomonas and Staphylococcus played an important role in the formation of biofilms an aggregates [78][79][80][81] .…”
Section: Discussionmentioning
confidence: 99%
“…The Methylobacterium strain DSM 18358 (DSMZ: Deutsche Sammlung von Mikroorganismen und Zellkulturen, Leibniz-Institute, Braunschweig, Germany) was chosen for experimental analysis in this study. The strain was cultured as described in an earlier study [49]. Two sets of experiments were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…A number of species, such as Methylobacterium species [12], Acinetobacter calcoaceticus [4], and Mycobacterium species [12,14], have been implicated in promoting bacterial aggregation in pure or simple mixed cultures. Specifically, the Methylobacterium DSM 18358 was previously proved to be a key strain in the formation of aggregates in drinking water and, subsequently, in the formation of biofilms on available surfaces exposed to drinking water [49]. Thus, in this study the role of the motility of the Methylobacterium strain DSM 18358 in the interactions between drinking water bacteria was explored in agar plate experiments to understand if this is a significant factor for the communication between bacteria in drinking water.…”
Section: Introductionmentioning
confidence: 99%